Research handbook on the future of work and employment relations - Townsend, Keith, 1969-; Wilkinson, Adrian (Cheltenham, UK. : Edward Elgar, 2011)
The broad field of employment relations is diverse and complex and is under constant development and reinvention. This handbook, written by international scholars, discusses fundamental theories and approaches to work and employment relations, and their connection to broader political and societal changes.
Keywords: Industrial relations